Evaluating possible innovative and sustainable approach of mosque in contemporary world - Utaberta, Nangkula; Asif, Nayeem; Hamzah, Zabidi (Jabatan Seni Bina, Fakulti Kejuruteraan & Alam Bina, Universiti Kebangsaan Malaysia, 2016)
Mosque is one of the major establishment within a Muslim community in countries with Muslim majority as well as countries where Muslims are minority. It is almost inevitable that every Muslim community would have at least one mosque within the locality. For most of the cases in Muslim major countries, there are more than one mosque to be found in any locality. These carries the sign of different ideologies and isms of architecture according to their contextual variance. In contemporary world, where environmental issues are given high priority, identifying sustainable approach for designing mosques are strongly recommended. This paper aims to analyze the principles of Islamic teachings toward attaining a balanced built environment and its implication on developing a sustainable language for mosque architecture in contemporary world. It analyzes the indigenous characteristics of the Prophet's (pbuh) mosque and draws lessons from therein. It also presents discussion on the contemporary Polder Mosque in Netherlands and its innovative sustainable features. Recommendations are made consequently regarding sustainable approach of mosque design in the contemporary world at the end of this paper.